2020
DOI: 10.1111/plb.13116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant age on performance of the tropical perennial fodder grass,Cenchrus ciliarisL. subjected to elevated ultraviolet‐B radiation

Abstract: • Abiotic stress, notably high ultraviolet-B (eUV-B), limit growth and productivity of many crop plants, but information on response of forage grasses to eUV-B radiation is rather limited. • The present study was therefore conducted to increase our understanding of differential age-related responses on growth, metabolism and fodder quality of Cenchrus ciliaris-3108 (Buffel grass) to elevated UV-B (eUV-B: 7.2 kJÁm À2 Áday À1). • Plant growth at both growth stages was notably reduced in response to eUV-B, except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
(65 reference statements)
2
3
0
Order By: Relevance
“…The average ash content of the samples was 4.27%. This result is consistent with the results reported by Hamid et al [ 18 ], who stated that the values of Cenchrus ciliaris were between the range of 8.98% and 9.14%. The CP values of the grass fodder species were observed to be above the critical value of 7.5% which is reported to be required for proper digestion ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The average ash content of the samples was 4.27%. This result is consistent with the results reported by Hamid et al [ 18 ], who stated that the values of Cenchrus ciliaris were between the range of 8.98% and 9.14%. The CP values of the grass fodder species were observed to be above the critical value of 7.5% which is reported to be required for proper digestion ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…The average TDN content of grass fodder was 77.45% ( Table 3 ). A similar result was reported by Hamid et al [ 18 ], who reported that the values were in the range of 53.14% to 63.65% TDN, which provides an assessment of the energy content of the feed. The larger the value of TDN, the more energy is condensed within feedstuff.…”
Section: Discussionsupporting
confidence: 88%
“…Peng et al (2017) concluded that the abun dance of the flavone O-glucosides might be responsible for adaptation to UVB irradiance. Plants under UV-B had an increased total flavonoid content, as Hamid et al (2020) found in Cenchrus ciliaris L., because UV-B radiation led to synthesis of key enzymes of the phenylpropanoid pathway.…”
Section: Metabolites Related To Ros Detoxification Under Uvb Irradiationmentioning
confidence: 69%
“…An important question is whether plants can evolve rapidly to adapt to environmental change; if not, migration or extinction may be the only options during times of environmental change ( Davis et al., 2005 ). Plants have established multiple strategies to cope with the adverse effects of UV-B radiation; these include increasing the number of branches and tillers ( Hamid et al., 2020 ), synthesizing UV-absorbing substances ( Tohge et al., 2011 ; Kaling et al., 2015 ; Tohge and Fernie, 2017 ), and altering hormone homeostasis ( Vanhaelewyn et al., 2016 ; Yang et al., 2020 ; Miao et al., 2021 ). Our studies show that flavonoid biosynthesis is most highly associated with UV-B responses and can synergistically respond to multiple types of UV-B-induced stress.…”
Section: Discussionmentioning
confidence: 99%